Rolling back the state: public administration in the age of market supremacy - Bhattacharya, Mohit (1996)
The author, following a discussion on the background of World Bank sponsored rethinking on State's developmental role, spells out its implications in terms of the new political economy of development and the intellectual impasse that it has created. He follows up the discussion with a detailed critical account of a series of serious problems that it poses to nations pursuing the model of State-led development. He winds up the discussion drawing a political theoretic conclusion that future of public administration in the Third World depends on "who governs the State and how the governors seek to relate themselves to the phenomenon of globalisation and liberalisation". - Reproduced
Keywords: Public administration